The nexus of employee's commitment, job satisfaction, and job performance: An analysis of FMCG industries of Pakistan - Muhammad Asif Qureshi; Jawaid Ahmed Qureshi; Jalil Ahmed Thebo; Ghulam Mustafa Shaikh; Noor Ahmed Brohi; Shahzad Qaiser (Cogent Business & Management, 2019)
The purpose of this study is to analyze the dimensions of job satisfaction and organizational commitment by using a more comprehensive approach to address job performance. The structural equation modeling analyses have been used to analyze the data collected from managers of fast-moving consumer goods. This study strives to examine the role of normative organizational commitment, affective organizational commitment, and continuous organizational commitment in predicting individuals' job satisfaction, which further leads to job performance. The findings of the confirmatory factor analysis establish the excellent model fitness of the studied model. Furthermore, the results of structural equation modeling conclude that the significant association of all three forms of commitment to affect the job satisfaction of employees positively. The results indicate that normative commitment is the most influential form of organizational commitment, while continuous commitment is the least influential in impacting job satisfaction. Furthermore, the outcomes established a significant positive relationship between job satisfaction and job performance of employees of the fast-moving consumer goods sector of Pakistan.
Keywords: 650; employee commitment; job performance; job satisfaction; Pakistan